2009
DOI: 10.6090/jarq.43.129
|View full text |Cite
|
Sign up to set email alerts
|

Vibration and Shock Analysis of Fruit and Vegetables Transport-Cherry Transport from Yamagata to Taipei-

Abstract: Vibration and shock data was collected using accelerometers placed in corrugated fiberboard containers of cherries transported from Yamagata, Japan to Taipei, Taiwan. Vibration during airplane transport differed from that of transport by trucks, with much high-frequency vibration and the highest peak frequency measured at 80 Hz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…A PSD peak in the low‐frequency range (e.g. 2–5 Hz) was reported in studies conducted in India, Taipei and Thailand and is widely associated with suspension response . The results revealed that high speeds increased the suspension response of the normal load truck.…”
Section: Resultsmentioning
confidence: 70%
“…A PSD peak in the low‐frequency range (e.g. 2–5 Hz) was reported in studies conducted in India, Taipei and Thailand and is widely associated with suspension response . The results revealed that high speeds increased the suspension response of the normal load truck.…”
Section: Resultsmentioning
confidence: 70%
“…The effects on the produce were examined before and after the transport experiment. 15,31,51 This approach enabled the vibration parameters to be directly related to changes in produce quality, but the investigations were mostly restricted to data collected during a single transit trip.…”
Section: In-transit Experimentsmentioning
confidence: 99%
“…11,[14][15][16]52,79 Some researchers used a threshold for acceleration, and below the threshold the logging was not performed. 31,101 However, having a higher acceleration threshold may only capture the shocks instead of vibration. Continuous data logging without a set threshold is limited by the power or the memory capacity of the device, and the first to run out determines the time of continuous use for a device.…”
Section: Limited Time Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Because postharvest bruising is related to large product and nancial losses, abundant studies on bruise prevention, such as improved transportation techniques, from the viewpoint of suppliers have been conducted [6]. For instance, various researchers have examined physical factors related to damage such as packaging friction [6,13], vibration [14,15], and shock [16][17][18]. However, little research has focused on consumers' subjective evaluations of the quality of damaged products [11] and reported an association between visual attention to damaged apples and purchase intention.…”
Section: Introductionmentioning
confidence: 99%